Growth of Au@Ag Core–Shell Pentatwinned Nanorods: Tuning the End Facets. Issue 38 (9th August 2013) - Zhang, Weiqing; Goh, Hao Ying Johnny; Firdoz, Shaik; Lu, Xianmao
Abstract Au@Ag core–shell nanorods with tunable end facets are obtained by coating Au bipyramids (BPs) with Ag. The resultant nanorods exhibit a pentatwinned crystal structure with tips terminated with either {110} or {111} facets. The control over the end facets is achieved by varying the capping agents and tuning the reduction rate of Ag. Specifically, when Ag is reduced slowly, Au@Ag nanorods with flat {110} end facets are formed with cetyltrimethylammonium bromide (CTAB) as the capping agent. If CTAB is replaced with cetyltrimethylammonium chloride (CTAC), Au@Ag nanorods with tips terminated with {111} facets are obtained. However, at a high Ag reduction rate, dumbbell‐shaped Au@Ag nanorods are formed, with either CTAB or CTAC as the capping agent. The morphological evolution of the nanorods in each case is closely followed and a growth mechanism is proposed.